When a Laparoscopic Cholecystectomy becomes a Case of Medical Negligence? Supreme Court of India (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
It is now well-established that laparoscopic cholecystectomy is associated with a two to three times higher risk of bile duct injury (BDI) in comparison to open cholecystectomy. Moreover, BDI during cholecystectomy is a common cause of litigation of medical negligence against the surgeon. The complainant brought a medical negligence action against the surgeon Dr. Gurmit Singh (OP-1) and the OP-3. On 13.07.2004 the complainant’s wife approached R-1, a laparoscopic surgeon at Preet Surgical Centre & Maternity Hospital, R-2 for laparoscopic cholecystectomy. Due to a serious condition, the patient was shifted to DMC Ludhiana where she was treated under R-3. The complainant discussed the cause of death and the need for autopsy with R-3, however, he was told that the patient died due to intraoperative injuries to the colon and bile duct resulting in Peritonitis, Peritoneal Collection, Septicaemia and Multi-Organ failure. It is in the above-referred circumstances that the complainant filed a consumer complaint before the SCDRC, Punjab on 14.02.2005 for monetary compensation quantified at Rs. 62,85,160 from the Respondents for negligence and deficiency of services. The SCDRC after considering the evidence and hearing both the parties, allowed the complaint and held R-1 and 2 negligent and exonerated R-3 and 4. R-1 and 2 were directed to pay Rs.1544000 jointly and severally and Rs.10000 as costs. According to NCDRC, there was no negligence on the part of respondents. Supreme Court opined that the interest of justice would be subserved if R-1 and 2 are directed to pay to the complainants a total amount of Rs. 2500000 (Rupees Twenty Five Lakhs only) with interest @ 6% per annum from the date of SCDRC order as compensation.
Keywords: Surgeon; Ethics Committee; Medical record; Deficiency of service